Entrepreneurship : Hi- Jack Technology / Muhammad Faisal Muhamd Apardi ... [et al.] - Muhamd Apardi, Muhammad Faisal; Rahmat, Nur Azzammudin; Abdullah, Muhd Nur Azzammuddin; Mat Nor, Mohd Al Fadil; Zainuddin, Mohd Syafiq (2008)
This business if formed by five entrepreneurs in order to achieve the government integection to improve the small industry and technology among Bumiputra in our cormiyy Furthermore, we want to spread a new technology in our country. Therefore, our enterprise, Hi- Jack Technology SDN BHD would like to sell a new product, know as the “Motorized Cylinder Jack”.